Possibilities of statistical methodology in the study of economic security of the region - Dmitry V. Dianov; Elena A. Radugina (Статистика и экономика, 2019)
Economic security, following the physical protection and security rapidly broke into the life of modern domestic society. This is a huge, very theoretically capacious section of the management system and at the same time a variety of practical activities. As the state of any economic system, characterized by the ability to withstand any negative encroachment from any subject, institution, other systems, social environment, etc., both economic and financial security is estimated, in fact, a polygamous system of indicators on all aspects of financial and economic activity.Purpose: therefore, the purpose of this scientific work, defined as the improvement of information support structures, decision-making in relation to economic security, fully meets the needs of management science and practice.Materials and methods: At the same time, all the methods, necessary for the statistical study of economic and financial security are used in the work: at each stage, an extensive block of statistical tools is involved, represented by the methods of the general theory of statistics and mathematical statistics, including multidimensional groups – cluster analysis, correlation and regression methods. The official materials of the state statistics and Internal Affairs Bodies of the Russian Federation, as well as the official statistics of the Ministry of Economy and Finance of Moscow Region Government were used to perform practical calculations.Results: A key aspect of this research work is related to the selection and formation of a set of statistical indicators, which in the interconnection and addition gave a complete comprehensive picture of the existing relationships and established patterns. These are demographic and resource indicators, and the results and efficiency of the economic complex. The use of the designated statistical tools allowed obtaining such results as justification of analytical capabilities and approbation of statistical methods in the study of economic security of the Moscow region; formation of clusters, consisting of homogeneous municipal districts of the Moscow region, designated as clustering units; calculation of relative analytical indicators; construction and interpretation of regression models.Conclusion: the complex of the obtained results and conclusions, as well as the scientifically based algorithm of statistical tools application, tested in the work, are undoubtedly an important information component in the management of economic and financial security not only in the Moscow region, but also in any region, both in the Central Federal district and in the whole central Russia.